(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article deals with the issues of studying the functional characteristics of the body of student-sportsmen in the conditions of the Republic of Karakalpakstan. It is noted that the system-forming factor of functional reserves indicates the results of activities that ensure the adaptation of the body of student-sportsmen to various physical loads. It was found that the level of cardiac synchronization characterizes the degree of vegetative balance.